Differential Regulation of the Phenazine Biosynthetic Operons by Quorum Sensing in Pseudomonas aeruginosa PAO1-N - Higgins, Steven; Heeb, Stephan; Rampioni, Giordano; Fletcher, Mathew P.; Williams, Paul; Cámara, Miguel (Frontiers in Cellular and Infection Microbiology, 2018)
The Pseudomonas aeruginosa quorum sensing (QS) network plays a key role in the adaptation to environmental changes and the control of virulence factor production in this opportunistic human pathogen. Three interlinked QS systems, namely las, rhl, and pqs, are central to the production of pyocyanin, a phenazine virulence factor which is typically used as phenotypic marker for analysing QS. Pyocyanin production in P. aeruginosa is a complex process involving two almost identical operons termed phzA1B1C1D1E1F1G1 (phz1) and phzA2B2C2D2E2F2G2 (phz2), which drive the production of phenazine-1-carboxylic acid (PCA) which is further converted to pyocyanin by two modifying enzymes PhzM and PhzS. Due to the high sequence conservation between the phz1 and phz2 operons (nucleotide identity > 98%), analysis of their individual expression by RNA hybridization, qRT-PCR or transcriptomics is challenging. To overcome this difficulty, we utilized luminescence based promoter fusions of each phenazine operon to measure in planktonic cultures their transcriptional activity in P. aeruginosa PAO1-N genetic backgrounds impaired in different components of the las, rhl, and pqs QS systems, in the presence or absence of different QS signal molecules. Using this approach, we found that all three QS systems play a role in differentially regulating the phz1 and phz2 phenazine operons, thus uncovering a higher level of complexity to the QS regulation of PCA biosynthesis in P. aeruginosa than previously appreciated. Importance The way the P. aeruginosa QS regulatory networks are intertwined creates a challenge when analysing the mechanisms governing specific QS-regulated traits. Multiple QS regulators and signals have been associated with the production of phenazine virulence factors. In this work we designed experiments where we dissected the contribution of specific QS switches using individual mutations and complementation strategies to gain further understanding of the specific roles of these QS elements in controlling expression of the two P. aeruginosa phenazine operons. Using this approach we have teased out which QS regulators have either indirect or direct effects on the regulation of the two phenazine biosynthetic operons. The data obtained highlight the sophistication of the QS cascade in P. aeruginosa and the challenges in analysing the control of phenazine secondary metabolites.